Discovery of β-d-2′-deoxy-2′-dichlorouridine nucleotide prodrugs as potent inhibitors of hepatitis C virus replication. Issue 15 (1st August 2017) - Pinho, Pedro; Kalayanov, Genadiy; Westerlind, Hans; Rosenquist, Åsa; Wähling, Horst; Sund, Christian; Almeida, Maria; Ayesa, Susana; Tejbrant, Jan; Targett-Adams, Paul; Eneroth, Anders; Lindqvist, Annelie
Graphical abstract: Abstract: Discovery of sofosbuvir has radically changed hepatitis C treatment and nucleoside/tide NS5B inhibitors are now viewed as one of the key components in combination therapies with other direct-acting antiviral agents. As part of our program to identify new nucleoside inhibitors of HCV replication, we now wish to report on the discovery of β-d -2′-deoxy-2′-dichlorouridine nucleotide prodrugs as potent inhibitors of HCV replication. Although, cytidine analogues have long been recognized to be metabolized to both cytidine and uridine triphosphates through the action of cytidine deaminase, uridine analogues are generally believed to produce exclusively uridine triphosphate. Detailed investigation of the intracellular metabolism of our newly discovered uridine prodrugs, as well as of sofosbuvir, has now revealed the formation of both uridine and cytidine triphosphates. This occurs, not only in vitro in cell lines, but also in vivo upon oral dosing to dogs.